Randomized Controlled Trial Comparing 1-Year Outcomes of Low-Energy Femtosecond Laser-Assisted Cataract Surgery versus Conventional Phacoemulsification - Liu, Yu-Chi; Setiawan, Melina; Chin, Jia Ying; Wu, Benjamin; Ong, Hon Shing; Lamoureux, Ecosse; Mehta, Jodhbir S. (Frontiers in Medicine, 2021)
Purpose: To compare 1-year clinical outcomes, phacoemulsification energy, aqueous profiles, and patient-reported outcomes of low-energy femtosecond laser-assisted cataract surgery (FLACS) versus conventional phacoemulsification. Methods: The study is a randomized controlled trial (RCT) with paired-eye design. Eighty-five patients were randomized to receive FLACS (Ziemer LDV Z8) in one eye and conventional phacoemulsification in the fellow eye. Clinical data including phacoemulsification energy parameters (cumulative dissipated energy, phacoemulsification power, and phacoemulsification time), uncorrected and corrected distance visual acuities (UCDVA and BCDVA), manifest refraction spherical equivalent (MRSE), central corneal thickness (CCT), endothelial cell count (ECC), anterior chamber flare, and postoperative complications were obtained for 1 year. Aqueous humor was collected for the analysis of prostaglandin (PGE)2, cytokines and chemokines concentrations. Patients’ reported-outcomes on surgical experiences were evaluated using an in-house questionnaire. Results: Compared to conventional phacoemulsification, the low-energy assisted FLACS group had significantly less ECC reduction at 3 months (1.5±0.3% versus 7.0±2.4%; P<0.01) and 1 year (8.2±2.8% versus 11.2±3.6%; P=0.03). There were no significant differences in the phacoemulsification energy parameters, UCDVA, BCDVA, MRSE, CCT, occurrence of postoperative complications between the 2 groups throughout postoperative 1 year. Patients’ subjective surgical experiences, including the surgical duration and perceived inconvenience, were comparable between the 2 groups. FLACS resulted in significantly higher aqueous PGE2 (P<0.01), interleukin (IL)-6 (P=0.03), IL-8 (P=0.03) and interferon (IFN)- (P=0.04) concentrations and greater anterior chamber flare at 1 day (P=0.02). Conclusions: Our RCT presented 1-year longitudinal clinical and laboratory data. The long-term ECC result was more favorable in low-energy FLACS. The rest of the intraoperative and postoperative outcomes, as well as patient-reported outcomes, were comparable between these two procedures. (RCT registered number: NCT03351894. https://clinicaltrials.gov/ct2/show/NCT03351894)